Native American communities in Wisconsin, 1600-1960 : a study of tradition and change - Bieder, Robert E. (Robert Eugene), 1938- (North Coast Books., 1995)
"The first comprehensive history of Native American tribes in Wisconsin, this thorough and eminently readable account follows Wisconsin's Indian communities - Ojibwa, Potawatomie, Menominee, Winnebago, Oneida, Stockbridge-Munsee, and Ottawa - from the 1600s through 1960. Written for students and general readers, it covers in detail the ways that native communities have striven to shape and maintain their traditions in the face of enormous external pressures." "The author, Robert E. Bieder, begins by describing the Wisconsin region in the 1600s - both the natural environment, with its profound significance for Native American peoples, and the territories of the many tribal cultures throughout the region - and then surveys the impact of French, British, and, finally, American, contact. Using native legends and historical and ethnological sources, Bieder describes how the Wisconsin communities adapted first to the influx of Indian groups fleeing the expanding Iroquois Confederacy in eastern America and then surveys the arrival of fur traders, lumber men, and farmers. Economic shifts and general social forces, he shows, brought about massive adjustments in diet, settlement patterns, politics, and religion, leading to a redefinition of native traditions." "Historical photographs and maps illustrate the text, and an extensive bibliography has many suggestions for further reading."--Jacket.